Influence of smoking and alcohol on gastric chemokine mRNA expression in patients with Helicobacter pylori infection. Issue 4 (1st April 2001) - Shimoyama, T; Everett, S M; Fukuda, S; Axon, A T R; Dixon, M F; Crabtree, J E
Abstract : Aim —Chemokines that play a primary role in active inflammation are increased in gastric mucosa infected with Helicobacter pylori. Cigarette smoking increases the risk of peptic ulcer disease and gastric cancer, whereas alcohol might exert an antibacterial role. The aim of this study was to examine the association between smoking or alcohol consumption and mucosal chemokine mRNA expression in H pylori associated gastritis. Methods —Gastric biopsy specimens were obtained from 46 patients with dyspepsia who were infected with H pylori, and total RNA was extracted. Semiquantitative reverse transcription-polymerase chain reaction (RT-PCR) was performed to quantify the mRNA expression of three C-X-C chemokines (interleukin 8 (IL-8), growth related oncogene α (GROα), epithelial neutrophil activating protein 78 (ENA-78)) and two C-C chemokines (regulated on activation normal T cell expressed and secreted (RANTES) and monocyte chemotactic protein 1 (MCP-1)). Results —GROα and ENA-78 mRNA expression was significantly increased (p < 0.05) in 22 smokers compared with 24 non-smokers; however, no difference was seen in the expression of IL-8, RANTES, and MCP-1 mRNA. No differences were observed in chemokine mRNA expression in relation to alcohol consumption. Conclusions —The increased C-X-C chemokine mRNA expression seen in smokers might play a role in inducing enhanced inflammatory activity in gastritis and the consequent severe diseases associated with H pylori infection.